Development and field application of strongly resilient temporary plugging diversion agent for fracturing - Yi Liu; Renbao Chen; Jing Liu; Yangyang Yu; Kuanliang Zhu (Journal of Petroleum Exploration and Production Technology, 2024)
Abstract Temporary plugging diversion fracturing in multistage horizontal well is normally used to improve stimulation efficiency and increase production in unconventional reservoirs. Temporary plugging agent plays an important role in diversion fracturing. A strongly resilient temporary plugging diversion agent can improve the effectiveness of fracturing diversion. Therefore, a novel organosilicon temporary plugging diversion agent (QBZU) was developed through micellar copolymerization method. Self-synthesized strongly resilient temporary plugging diversion agent (QBZU gel) was prepared by using acrylamide, N, N′-methylene bisacrylamide, surfactants, organosilicon, ammonium persulfate and sodium bisulfite as chemical raw materials. The micellar copolymerization is investigated to overcome the incompatibility of hydrophobic organosilicon and water-soluble monomer by adding some appropriate surfactants. The experimental results indicated that the combination of sodium dodecyl sulphonate and Tween 80 provided excellent copolymerization results. The characteristics of compressive resistance, salt resistance, shearing resistance, resilience and degradation are superior compared with traditional rigid granular temporary plugging agent widely used in oilfields (QG hydrogel). According to the experimental evaluation results of QBZU, its pressure-bearing capacity can reach 56.3MPa, shearing strength can reach 410N, elastic modulus can reach 80MPa, and Poisson ratio can reach 0.48. Meanwhile, the main synthetic factors affecting the resilient performance of QBZU were investigated, including polymer concentration, organosilicon concentration and the types of surfactant. Based on the fracturing pressure curve and microseismic monitoring results, the plugging and fracture diversion effectiveness was further confirmed.